Gelatin; Switch back to Halal: A Mini-Review - Sharif, Rahat (PSM Biological Research, 2019)
Gelatin is a traditional functional protein with water-soluble properties and has the potential of forming transparent gels under certain conditions. The main source of gelatin is pigskin and is widely used in processed food and medicinal products. Though the use of food products adulterated with porcine-derived gelatin create concerns in the mind of Muslims community, as in Islam, it is not acceptable or literally, we call it Haram. However, in recent times initiatives have been taken in producing gelatin from Halal sources, such as fish, chicken and bovine slaughtered according to Islamic teachings. Therefore, we highlighted different porcine alternative derived gelatin sources and also methods to detect edible product adulterated with pork or other haram stuff. This review could be useful in providing information to a large number of audience and food processing companies to minimize or if possible eradicate the use of porcine-derived gelatin in commercial food and medicinal products.